The Brain Structure and Intrinsic Characters of Falsification Thinking in Conditional Proposition Testing - Zhang, Meng; Wang, Li; Zou, Feng; Wang, Yufeng; Wu, Xin (Frontiers in Human Neuroscience, 2021)
Wason's selection task (WST) as a representative of the field of conditional proposition testing has been explored by multiple disciplines for more than 50 years, but the neural basis of its key falsification thinking remains unclear. Considering that the accuracy of individuals in WST has the stability over time, we believe that falsification thinking has a specific brain structural basis and intrinsic neural characteristics. To test this hypothesis, we studied individuals who were able to complete the wason selection task using functional magnetic resonance imaging (fMRI) (using voxel based morphology analysis, VBM) and resting EEG (using microstate analysis, which can reflect stable cognitive characteristics of individuals) techniques. Firstly, VBM analysis found that, compared with the verification group, the gray matter volume (GMV) of the left inferior temporal gyrus and right superior temporal region of the falsification group was larger, whereas, the GMV in the cerebellum of the verification group was significantly larger than that of the falsification group. Subsequently, the results of the microstate analysis of resting EEG data showed that the contribution of the class A of the falsification group, which are closely related to the language network, are significantly higher than that of the verification group. Our structural MRI and EEG results consistently show that the structure and intrinsic activity pattern of temporal lobe in individuals with falsification thinking are specific. Furthermore, the findings may provide potential insights into the role of temporal lobe (which is also a brain region of language processing) in thought.